Diethyl 2-[(2-benzyl-1-phenylsulfonyl-1H-indol-3-yl)methylene]malonate - Kavitha, T. (International Union of Crystallography, 2008)
In the title compound, C(29)H(27)NO(6)S, the sulfonyl-bound phenyl ring is almost perpendicular to the indole ring system [dihedral angle = 87.96 (6)°], while the benzylphenyl ring is oriented at an angle of 76.8 (7)°. An intramolecular C—H⋯O hydrogen bond is observed. In the crystal structure, molecules are linked into a zigzag C(10) chain along the b axis by intermolecular C—H⋯O hydrogen bonds.